Investigation of Physical Properties, Solubility, Dissolution Profiles, and Flow Properties of Solid Dispersion Loading Cefixime Using Chitosan and Sodium Alginate - Mardiyanto; Fithri, Najma Annuria; Shiyan, Shaum; Satrio, Fakhri D. (Science and Technology Indonesia, 2025)
The co-grinding method has been used to produce solid dispersions that increase the solubility of drug substances by utilizing hydrophilic polymers. The purpose of this study was to evaluate the effect of chitosan and variations of sodium alginate as polymers on the dissolution rate of cefixime solid dispersion using the co-grinding technique. The cefixime solid dispersion formulation was made in three variations of sodium alginate formulas, namely 200 mg, 250 mg, and 300 mg. Sample characterization was carried out using XRD, FTIR, SEM, solubility testing, dissolution rate, and flow properties. The results showed that Formula 2 (F2) cefixime solid dispersion was the best formula because the degree of crystallinity decreased to 21.71%, and FTIR analysis showed the functional group interaction. Evaluation of cefixime solid dispersion showed changes in particle morphology. In addition, there was an increase in the transmittance percentage in SIF of 98.587 ± 0.019 and an increase in the dissolution rate of cefixime of 83.61%, an increase in the flow rate of 6.3 ± 0.14 grams/second, an angle of repose of 26.4 ± 0.4◦, a compressibility index of 16.3 ± 0.29%, and a Hausner ratio of 1.19 ± 0.35.